1996
DOI: 10.1002/(sici)1098-2361(1996)15:5<499::aid-zoo6>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diets fed to southeast Asian colobines in North American and European zoos, with emphasis on temperate browse composition

Abstract: In May and June 1994 a survey of diets fed to captive southeast Asian colobines in European (n = 12) and North American (n = 9) zoos was conducted. Most diets were very complex, comprising an average of 25 ingredients; 149 different foods were listed in responses. Comparison of diets fed showed that European zoos feed a greater variety of fruits and vegetables, and fewer browse plants, than North American zoos. No standardized diet recommendations, based on ingredient or nutrient composition, are currently ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…While the present study cannot test mechanism, we posit that the observed patterns are strongly influenced by diet. Captive NHP diets contain reduced amounts of structural carbohydrates and plant toxins compared to wild diets (Clayton et al, ; Conklin‐Brittain & Wrangham, ; Dierenfeld, Koontz, & Goldstein, ; Nijboer & Dierenfeld, ), and folivorous diets are particularly difficult to replicate in captivity. For example, in the wild, leaves comprise ~70% of the A. caraya diet and ~61% of the C. guereza diet (Di Fiore et al, ; Fashing, ).…”
Section: Discussionmentioning
confidence: 99%
“…While the present study cannot test mechanism, we posit that the observed patterns are strongly influenced by diet. Captive NHP diets contain reduced amounts of structural carbohydrates and plant toxins compared to wild diets (Clayton et al, ; Conklin‐Brittain & Wrangham, ; Dierenfeld, Koontz, & Goldstein, ; Nijboer & Dierenfeld, ), and folivorous diets are particularly difficult to replicate in captivity. For example, in the wild, leaves comprise ~70% of the A. caraya diet and ~61% of the C. guereza diet (Di Fiore et al, ; Fashing, ).…”
Section: Discussionmentioning
confidence: 99%
“…The natural diet of this primate mainly consists of various types of leaves, but fruit is also consumed (5). Francois langurs and other leaf-eating primates of the subfamily Colobinae have a stomach consisting of different compartments for pregastric fermentation Like many other langur species, the Francois langur is threatened by extinction both in the wild (5) and in captivity (6). To increase the survival of these species in captivity, proper dietary management is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The endemic form of this disease, however, occurs mostly in the wet and humid tropics, where the climatic conditions may be more advantageous for the rapid multiplication of this pathogen in the environment (3,4,5). In the temperate zones of the world, this form may occur in geographical areas with a relatively high humidity (1,6,7,9,16). As far as we know, however, an epidemic of algal mastitis has not been reported on large-scale dairy farms in countries with relatively dry continental climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions on the nutritional management of captive leaf-eating primates stress the importance of a high-fiber diet to promote animal health and well being Edwards et al, 1990Edwards et al, , 1999. Some institutions with seasonal browse availability have adopted the use of local woody plant species as a supplement to a commercial biscuit and produce diet [Nijboer and Dierenfeld, 1996]. The addition of browse is intended to increase the fiber content of the captive diet and/or to provide behavioral enrichment via provision of a "natural" food item.…”
Section: Introductionmentioning
confidence: 99%